ChemInform Abstract: Synthesis of Tetrahydropyrazolo[1, 5‐c]pyrimidine‐2, 7(1H, 3H)‐diones. Issue 26 (6th June 2013) - Groselj, Uros; Podlogar, Anja; Novak, Ana; Dahmann, Georg; Golobic, Amalija; Stanovnik, Branko; Svete, Jurij
Abstract A straightforward synthesis of the title compounds (VII) and (XII) is presented.